Pengembangan Modul Bimbingan dan Konseling Berwawasan Merdeka Belajar Untuk Meningkatkan Penyesuaian Diri Mahasiswa Baru - Rizky Andana Pohan (Jurnal Counseling Care, 2023)
Adjustment is a global problem faced by almost all college freshmen in the world. Modules are one of the psychological assistance interventions that can help freshmen to improve the adaptation process. Kampus merdeka is a higher education policy program implemented by each university. The purpose of the study is to provide a narrative of the guidance and counseling module with an independent learning perspective in improving the self-adjustment of freshmen that meets the content and methodological requirements and describes the level of application by counselors in the guidance and counseling service unit of higher education. The research method used Research and Development model Analyze, Design, Development, Implementation, and Evaluation (ADDIE). The research was conducted by testing the development product in the form of a module with Focus Group Discussion. Data were analyzed using descriptive analysis. The development results show that the guidance and counseling module with an independent campus insight to improve the self-adjustment of freshmen is considered accommodating and effective to be applied to freshmen by counselors at the college level. Based on these findings, the prototype of the guidance and counseling module with an independent campus insight to improve the self-adjustment of freshmen can be used by counselors to help freshmen improve their adjustment in college. Keywords: Guidance & Counseling Module, Kampus Merdeka, Adjustment, Freshmen